Customs broker exam study guide & how to start your own CHB business thru Apr. 2015 exam edition - Sasaki, Jon K. (CHB Solution, 2015)
The Customs Broker Exam Study Guide helps the student to optimize his and her study time by isolating and emphasizing the most important sections of study reference material and by intentionally acknowledging then disregarding the less significant exam reference material. The book also methodically provides step-by-step guidance through the process of setting up one's own customs brokerage operation-as documented and successfully accomplished by an actual customs broker.